Colorectal Cancer-Associated Immune Exhaustion Involves T and B Lymphocytes and Conventional NK Cells and Correlates With a Shorter Overall Survival - Sorrentino, Carlo; D’Antonio, Luigi; Fieni, Cristiano; Ciummo, Stefania Livia; Di Carlo, Emma (Frontiers in Immunology, 2021)
Colorectal cancer (CRC) is one of the most common cancer worldwide, with a growing impact on public health and clinical management. Immunotherapy has shown promise in the treatment of advanced cancers, but needs to be improved for CRC, since only a limited fraction of patients is eligible for treatment, and most of them develop resistance due to progressive immune exhaustion. Here, we identify the transcriptional, molecular, and cellular traits of the immune exhaustion associated with CRC and determine their relationships with the patient’s clinic-pathological profile. Bioinformatic analyses of RNA-sequencing data of 594 CRCs from TCGA PanCancer collection, revealed that, in the wide range of immune exhaustion genes, those coding for PD-L1, LAG3 and T-bet were associated (Cramér’s V=0.3) with MSI/dMMR tumors and with a shorter overall survival (log-rank test: p=0.0004, p=0.0014 and p=0.0043, respectively), whereas high levels of expression of EOMES, TRAF1, PD-L1, FCRL4, BTLA and SIGLEC6 were associated with a shorter overall survival (log-rank test: p=0.0003, p=0.0188, p=0.0004, p=0.0303, p=0.0052 and p=0.0033, respectively), independently from the molecular subtype of CRC. Expression levels of PD-L1, PD-1, LAG3, EOMES, T-bet, and TIGIT were significantly correlated with each other and associated with genes coding for CD4+ and CD8+CD3+ T cell markers and NKp46+CD94+EOMES+T-bet+ cell markers, (OR >1.5, p<0.05), which identify a subset of group 1 innate lymphoid cells, namely conventional (c)NK cells. Expression of TRAF1 and BTLA co-occurred with both T cell markers, CD3γ, CD3δ, CD3ε, CD4, and B cell markers, CD19, CD20 and CD79a (OR >2, p<0.05). Expression of TGFβ1 was associated only with CD4+ and CD8+CD3ε+ T cell markers (odds ratio >2, p<0.05). Expression of PD-L2 and IDO1 was associated (OR >1.5, p<0.05) only with cNK cell markers, whereas expression of FCRL4, SIGLEC2 and SIGLEC6 was associated (OR >2.5; p<0.05) with CD19+CD20+CD79a+ B cell markers. Morphometric examination of immunostained CRC tissue sections, obtained from a validation cohort of 53 CRC patients, substantiated the biostatistical findings, showing that the highest percentage of immune exhaustion gene expressing cells were found in tumors from short-term survivors and that functional exhaustion is not confined to T lymphocytes, but also involves B cells, and cNK cells. This concept was strengthened by CYBERSORTx analysis, which revealed the expression of additional immune exhaustion genes, in particular FOXP1, SIRT1, BATF, NR4A1 and TOX, by subpopulations of T, B and NK cells. This study provides novel insight into the immune exhaustion landscape of CRC and emphasizes the need for a customized multi-targeted therapeutic approach to overcome resistance to current immunotherapy.